Not in front of the children? An analysis of sex on screen in Italy - Chiaro, Delia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Despite the fact that both state owned (RAI) and privately owned (Mediaset) Ital-ian television channels habitually adopt scantily dressed women in provocative poses to fulfill a purely decorative function on daytime television, a closer look at Italian TV reveals that it is far less liberated than it seems. In fact, in stark contradiction to the apparent unrestraint of autochthonous studio productions, references to sex and sexuality in imported fictional products tend to be severely mitigated in their translated forms. Furthermore, it also appears that sexual behaviour beyond traditional male/female ‘mainstream’ sexual practices becomes in-creasingly taboo in translation, as they too are either toned down or totally eliminated. Relegated to cable and satellite channels or late-night/early morning viewing on one of the privately owned Mediaset channels, programs containing very explicit sexual content such as US produced ‘Sex and the City’ are moderated quite significantly for Italian audiences, not only in terms of the pervasive use of strong, taboo language, but also for explicit references to a variety of sexual practices.This paper will discuss the norms which govern the translation of ‘adult’ materials for Italian TV both from an examination of the linguistic content of the programs themselves and from the point of view of operators involved in the dubbing process.